2022
DOI: 10.1177/17835917221088770
|View full text |Cite
|
Sign up to set email alerts
|

A Difference-In-Difference Approach to Estimate the Price Effect of Market Entry in High-Speed Rail

Abstract: The effect of competition on prices in the passenger transport sector can be difficult to estimate because of many influencing factors such as state regulation, demand, seasonality, and reactions of indirect competitors. A case of great interest in the rail sector is Italy, where on-track competition in the high-speed segment has been in place for nearly ten years. The paper aims at answering the question whether—and how much—incumbent’s prices are affected when competition starts on a route previously in mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…In other cases, the effect is more complex. In a recent detailed study, Beria et al (2022) showed that price on the Turin-Venice route decreased by -21% to -26% after the entry of Italo in May 2018. However, more than six months afterwards, the reduction was around 15%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In other cases, the effect is more complex. In a recent detailed study, Beria et al (2022) showed that price on the Turin-Venice route decreased by -21% to -26% after the entry of Italo in May 2018. However, more than six months afterwards, the reduction was around 15%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The group affected by the change is called the "treatment group" then the other is the "comparison group". The method is especially well adapted to our case study and has been already applied to railway analysis by Beria et al (2022). The authors compared routes in Italy with competition to routes without competition to better assess the effect of competition on price.…”
Section: The Difference-in-difference Approachmentioning
confidence: 99%
See 3 more Smart Citations